2017
DOI: 10.1007/s12035-017-0636-x
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Role of Nurr1 Activation and Thrombin Inhibition in the Neuroprotective Effects of Dabigatran Etexilate in Rotenone-Induced Parkinson’s Disease in Rats

Abstract: Recently, it has been shown that both decreased nuclear receptor-related 1 (Nurr1) expression and thrombin accumulation are involved in the degeneration of dopaminergic neurons in Parkinson's disease (PD). The new anticoagulant dabigatran etexilate (DE) is a direct thrombin inhibitor that owns benzimidazole group, which has been proposed to activate Nurr1. In the present study, we examined the neuroprotective effects of DE in rotenone model of PD. Rotenone was injected subcutaneously at a dose of 1.5 mg/kg eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…In this study, rotenone caused a substantial decrease in Nurr1 mRNA expression in the SN with a subsequent decline in TH and VMAT levels and suppression of GDNF/c‐Ret signalling, which contributed to the observed nigral neuronal injury and striatal DA reduction. These results are consistent with other studies that showed a reduction in Nurr1 together with Nurr1‐related genes in PD models . The decrease in Nurr1 expression in PD rats could be due to rotenone‐induced α‐synuclein accumulation, which regulates the degradation of Nurr1 protein .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, rotenone caused a substantial decrease in Nurr1 mRNA expression in the SN with a subsequent decline in TH and VMAT levels and suppression of GDNF/c‐Ret signalling, which contributed to the observed nigral neuronal injury and striatal DA reduction. These results are consistent with other studies that showed a reduction in Nurr1 together with Nurr1‐related genes in PD models . The decrease in Nurr1 expression in PD rats could be due to rotenone‐induced α‐synuclein accumulation, which regulates the degradation of Nurr1 protein .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our previous work revealed decreased expression of nuclear receptor related 1 (Nurr1) in an animal model of rotenone‐induced PD and this has been suggested to contribute to the degeneration of dopaminergic neurons . Nurr1 is a transcription factor that is related to the nuclear receptor superfamily and is expressed predominantly in the central nervous system, especially in the substantia nigra (SN) .…”
Section: Introductionmentioning
confidence: 99%
“…Creatine [179,180] Cudraflavone B [181] Curcumin [89,117,[182][183][184] Cyanidin [185,186] D-512 [187] D-607 (bipyridyl-D2R/D3R agonist hybrid) [12,188,189] DA-2 (8D) [12,89] DA-3 [12] DA-4 [12] Dabigatran etexilate [190] Dabrafenib [191] (S)-3,4-DCPG [115] Deferasirox [24] Deferricoprogen [192] Delphinidin [160,185,193,194] Demethoxycurcumin [195] Dendropanax morbifera active compound [196] Desferrioxamine (Desferoxamine, Desferal, DFO) [112] (S)-N-(3-(3,6-Dibromo-9H -carbazol-9-yl)-2-fluoropropyl)-6-methoxypyridin-2-amine [197] 4,5-O-Dicaffeoyl-1-O-(malic acid methyl ester)-quinic acid derivatives (R1, R2, R3, R4, or R5 = caffeoyl) [198] Dihydromyricetin [199]…”
Section: -O-(3-chloropivaloyl)mentioning
confidence: 99%
“…Several studies have reported an association between an increased atherosclerosis-related [ 34 ] inflammation markers [(e.g. TNF-α [ 33 ] and an increased risk of neurodegenerative diseases [ 32 ], including stroke [ 34 ], dementia and PD [ 35 ]. The level of TNF-α increased in the ACOS cohort [ 36 ] and its value is higher than the control groups [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aging [ 45 ] and atherosclerosis-related diseases of ACOS cohort are associated with the system inflammation [ 31 ] also. Considering these speculations [ 30 , 35 , 39 ]; aging, hypoxemia [ 16 , 42 ] and system inflammation [ 14 , 31 ] are predisposing factors [ 33 ] for neurodegenerative diseases (e.g. stroke) even without the comorbidities.…”
Section: Discussionmentioning
confidence: 99%